1999
DOI: 10.1136/bmj.318.7196.1451
|View full text |Cite
|
Sign up to set email alerts
|

Sequential randomised and double blind trial of promethazine prophylaxis against early anaphylactic reactions to antivenom for bothrops snake bites

Abstract: Objective To investigate the efficacy of the H 1 antihistamine promethazine against early anaphylactic reactions to antivenom. Design Sequential randomised, double blind, placebo controlled trial. Setting Public hospital in a venom research institute, São Paulo, Brazil. Participants 101 patients requiring antivenom treatment after being bitten by bothrops snakes. Intervention Intramuscular injection of promethazine (25 mg for adults and 0.5/kg for children) or placebo given 15-20 min before starting intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
4
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 15 publications
5
45
4
3
Order By: Relevance
“…In this way, antivenom is routinely given, in our hospital, in patients in which necrosis is still not present. The proportion of early anaphylactic reactions was not exceptionally high and similar to that observed for other antivenoms 10,12 , and manifestations were promptly reversed by proper measures.…”
Section: Discussionmentioning
confidence: 61%
“…In this way, antivenom is routinely given, in our hospital, in patients in which necrosis is still not present. The proportion of early anaphylactic reactions was not exceptionally high and similar to that observed for other antivenoms 10,12 , and manifestations were promptly reversed by proper measures.…”
Section: Discussionmentioning
confidence: 61%
“…Subcutaneous adrenaline premedication produced a significant reduction in the incidence of early adverse reactions, and the effect was preserved when stratified for severity (23). But antihistamine appears to be of no obvious benefit in preventing acute reactions from antivenom (24). There is also no good evidence that hydrocortisone should be given before antivenom (25).…”
Section: Discussionmentioning
confidence: 92%
“…Although few patients presented skin rash, no anaphylaxis occurred in these 35 patients. However, in the last decade, studies of the efficacy and safety of premedication strategies have been conducted in Sri Lanka and Brazil (23,24). Subcutaneous adrenaline premedication produced a significant reduction in the incidence of early adverse reactions, and the effect was preserved when stratified for severity (23).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to prevent early reactions which included pretreatment with epinephrine, anti-histaminics, corticosteroids and reduction in speed and concentration of intravenous antivenom administration have not been effective in adequately designed clinical trials. 13,14,15 However the studies by Premawardhena et al, 16 Gawarammana et al 17 and de Silve et al 18 have shown the efficacy of low dose adrenaline and combination of chlorpheniramine and hydrocortisone in reduction of antivenom reactions. A recent systematic review and meta-analysis 19 has shown the beneficial role of premedication with adrenaline in reduction of early antivenom reactions.…”
Section: Late Serum Sickness Type Reactionsmentioning
confidence: 95%